Sump syndrome: Diagnosis dilemmas and therapeutic approaches—A case series - Shahem Abbarh (17945564) (2024)
Key Clinical Message It is important to consider the diagnosis of Sump syndrome in patients with a history of open cholecystectomy, particularly in those who migrate from developing countries where alternative biliary interventions may be limited. The presentation may range from acute severe, mimicking acute ascending cholangitis, to chronic recurrent abdominal pain without evidence of inflammation. Management is a case‐by‐case decision, with principal management aims to decompress the biliary tract and address any underlying sepsis. Sump syndrome is a rare and often long‐term complication of choledochoduodenostomy (CDD). The presentation and severity are variable, and management should be tailored to each patient based on several factors. Herein, we report three cases of sump syndrome, each demonstrating unique diagnostic dilemmas and therapeutic modalities. Case I describes a woman presenting with acute cholangitis, managed with percutaneous transhepatic cholangiography (PTC) and endoscopic retrograde cholangiopancreatography (ERCP). Case II illustrates a similar presentation complicated by myocardial infarction, necessitating urgent biliary decompression via PTC and subsequent unsuccessful endoscopic stenting. Case III highlights the diagnostic difficulty in a stable patient with inconclusive diagnostic imaging. This case series emphasizes the importance of considering sump syndrome diagnosis in patients with a history of CDD or open cholecystectomy, especially in elderly patients and those who come from regions where alternative biliary interventions may be limited. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.9378